Synchronous Periampullary Tumors in a Patient With Pancreas Divisum and Neurofibromatosis Type 1 - Gregório, Cleandra; Rosset, Clévia; Alves, Laura da Silva; Netto, Cristina Brinkmann Oliveira; Machado, Simone Marcia dos Santos; Bersch, Vivian Pierri; Osvaldt, Alessandro Bersch; Ashton-Prolla, Patricia (Frontiers in Genetics, 2020)
In this study, we describe for the first time a Neurofibromatosis type 1 patient with pancreas divisum, multiple periampullary tumors and germline pathogenic variants in NF1 and CFTR genes. Case report: A 62-year-old female NF1 patient presented with weakness, choluria, nausea, and diffuse abdominal pain to an emergency room service. Magnetic resonance imaging revealed an abdominal mass involving the periampullary region and pancreas divisum. After surgical resection, three synchronous neoplasms were detected including two ampullary tumors (adenocarcinoma of the major ampulla and a neuroendocrine tumor of the minor ampulla) and a gastrointestinal stromal tumor (GIST). Germline multigene panel testing (MGPT) identified two pathogenic heterozygous germline variants: NF1 c.838del and CFTR c.1210-34TG[12]T[5]. Conclusions: This is the first report of a Neurofibromatosis type 1 patient with pancreas divisum and multiple periampullary tumors harboring pathogenic germline variants in NF1 and CFTR genes. The identification of two germline variants and a developmental anomaly in this patient may explain the unusual and more severe findings and underscores the importance of comprehensive molecular analyses in patients with complex phenotypes.